Mendiants, vagabonds et la contagion du crime en France : des représentations aux réalités sociales (1789-1914) - Antony Kitts (Criminocorpus)
Since the Middle Ages, the figures of poverty and marginality have aroused ambivalent reactions within French society, permanently torn between compassion and fear. The long nineteenth century did not escape these prejudiced feelings against the beggar and the vagrant, taking on an unprecedented dimension in the years 1880-1890 when the question of recidivism became acute. Faced with this "army of crime", experts of all kinds - alienists, doctors, psychiatrists, criminologists, magistrates, police officers and journalists - took up this burning social issue in a climate of insecurity and collective psychosis. They accuse them of all the evils and plagues (contagious diseases, petty crime, theft, prostitution, etc.) to explain the reasons why they indulge in this asocial state, placing them outside the dominant social norms. Thus, behind these discourses of exclusion and hatred, revealing a medicalization and a criminalization of wandering, the analysis of these impoverished and marginalized men and women reveals a more nuanced social reality that is linked to the working classes vulnerable to economic upheavals and the vagaries of life.